2016
DOI: 10.21608/eijest.2016.97183
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Recycling of Aluminum Alloy (AA-6061) Chips via Hot Extrusion Followed by Equal Channel Angular Pressing (ECAP)

Abstract: Aluminum alloy (AA-6061) chips were recycled using hot extrusion followed by equal channel angular pressing (ECAP) process at room temperature. AA-6061chips were cold compacted into billets, then extruded into rods under extrusion ratio of 5.2 at different extrusion temperatures (ET). Finally, the rods were processed through ECAP die with inner angle Φ of 90°, and outer arc angle Ψ of 32.8°, which impose strain ɛ of 1 per each pass up to different number of passes. The effects of the ECAP number of passes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
(61 reference statements)
4
11
0
Order By: Relevance
“…So, there were no further increases after 5% B4C and the 4 th pass of hot ECAP. Rifai et al (2014) and Selmy et al (2016) confirmed with their observations that the improvement on the MMCs matrix is related to the good bonding between chips and particles during the ECAP process, in which the extensive materials deformations broke up the oxide films on the surface of the sample. Therefore, the material surface ensures better contact bonding between chips.…”
Section: Compressive Strength Testsupporting
confidence: 75%
See 1 more Smart Citation
“…So, there were no further increases after 5% B4C and the 4 th pass of hot ECAP. Rifai et al (2014) and Selmy et al (2016) confirmed with their observations that the improvement on the MMCs matrix is related to the good bonding between chips and particles during the ECAP process, in which the extensive materials deformations broke up the oxide films on the surface of the sample. Therefore, the material surface ensures better contact bonding between chips.…”
Section: Compressive Strength Testsupporting
confidence: 75%
“…The recycled MMCs after pass four had the highest hardness value, and the overall hardness values gradually increased as a result of increasing the sample's number of passes. The main reason for the material hardness values enhancement was the presence of the total strain and die fraction on the high angle boundaries (Haghighi et al 2012;Selmy et al 2016). The highest value of hardness was achieved for 4 th pass, and it is due to the material work hardening, which results in the formation at the initial stage of the hot ECAP process.…”
Section: Hardness Testmentioning
confidence: 99%
“…It consists of coarse-grained structure with grain size of about 48 m. On the other hand, the microstructure of the hot extruded specimen consists of fine grains of about 13.5 m, as shown in Figure 2(b). The finer grained microstructure is caused by severe plastic strain imposed during the recycling processes and the positive effect of chip boundaries which can act as barriers between grains to prevent grain growth [25][26][27][28]. The decrease in grain size was congruent with previous work done by Haase et al [25] where the grain size of the as-received AA-6060 alloy was 385 m, while it was 31.8 m for the hot extruded chips at 450 ∘ C. Also, Selmy et al [26,27] recycled AA-6061 chips through hot extrusion; the grain size was 48 m for as-received samples while it was 15.8 and 10.9 m for the recycled samples produced by hot extrusion at 500 and 350 ∘ C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations of visible chips boundary and micro-voids in the recycled AA6061 chips were obtained by Refs. 19,20 In Figure 7(b), it can be observed that the number of chips boundary and the micro-voids increases during the loading deformation. Furthermore, damage evolution is clearly observed in Figure 7, where the micro-cracks and dimples are formed due to the coalescence and growth of the micro-voids.…”
Section: Tensile Behaviourmentioning
confidence: 93%